The SmartVision Navigation Prototype for Blind Users - du Buf, J. M. H. (2011)
The goal of the Portuguese project "SmartVision: active vision for the blind" is to develop a small, portable and cheap yet intelligent and reliable system for assisting the blind and visually impaired while navigating autonomously, both in- and outdoor. In this article we present an overview of the prototype, design issues, and its different modules which integrate GPS and Wi-Fi localisation with a GIS, passive RFID tags, and computer vision. The prototype addresses global navigation for going to some destiny, by following known landmarks stored in the GIS in combination with path optimisation, and local navigation with path and obstacle detection just beyond the reach of the white cane. The system does not replace the white cane but complements it, in order to alert the user to looming hazards. In addition, computer vision is used to identify objects on shelves, for example in a pantry or refrigerator. The user-friendly interface consists of a four-button hand-held box, a vibration actuator in the handle of the white cane, and speech synthesis. In the near future, passive RFID tags will be complemented by active tags for marking navigation landmarks, and speech recognition may complement or substitute the vibration actuator.